On language, culture, and controversies. Issue 3 (2nd September 2018) - Bouchard, Jeremie
ABSTRACT: Controversies in applied linguistics are often products of clashes between diverging theoretical perspectives. To overcome controversies and aim towards new forms of knowledge, academics and practitioners therefore need to adopt interdisciplinary approaches to addressing theoretical issues at the heart of controversies, so as to find threads within and across epistemologies and further clarify objects under investigative scrutiny. From this perspective, this essay presents the controversy over whether English as a lingua franca (ELF) constitutes a valid approach to English language learning and teaching as the outcome of conflicting theoretical understandings of language. The article also provides a realist view of language as a stratified and emergent social phenomenon. Finally, some preliminary observations regarding the adoption of a realist approach to ELF-oriented education are offered.